Perceived Impact of Climate Change on Swamp Rice Cultivation by Farmers in Ebonyi State, Southeastern Nigeria - B. E. Diagi; M. O. Nwagbara (Archives of Current Research International, 2018)
The perception of changes in climate in any environment by farmers significantly influences their ability to adjust and cope with challenges that might emerge from such changes. Climate change can have direct impact on swamp rice cultivation because swamp rice cultivation in Ebonyi State is rain-fed. This impact is particularly significant as swamp rice farming constitutes a major source of income and employment in the area. The study thus examined the perceived impact of climate change on swamp rice cultivation by farmers in Ebonyi State, Southeastern Nigeria and compare with meteorological data. Data used for the study were obtained through the administration of 505 copies of structured questionnaire to swamp rice farmers in the three agricultural zones of the State. Also, data on rainfall and temperature were sourced from the archive of Nigerian Meteorological Agency, Oshodi, Lagos covering a period of 31 years. Primary data obtained were analysed using descriptive statistics. Results showed that 82.6% of the respondents were aware of climate change; 81.8% claimed to have noticed change in climate in the last two decades; 50.9% of the farmers have noticed an increase in farm size. However, 79.0% of the respondents were of the view that change in rainfall is responsible for the increase noticed in farm size. Climatic trends show a positive trend and the 2-year moving average suggests an increase in temperature and rainfall over the 31 years. Climatic trends confirmed farmers’ perceptions that temperature and rainfall are increasing. Overall impacts of climate change on swamp rice cultivation appear to be positive as farmer’s perception of climate change is consistent with meteorological data. With increasing swamp size in the area as a result of increased rainfall, it becomes compelling that wealthy individuals, corporate bodies and government should direct more investments to swamp rice farming in Ebonyi State in order to boost food security, employment and consequently income generation for the area and Nigeria in general.